A Narrative Review of How Students Perceive a Good Teacher - Tang, Kuok Ho Daniel (Acta Pedagogia Asiana, 2025)
Students come to class with various perceptions of what constitutes a good teacher. These affect how a teacher is evaluated in increasingly student-centered classrooms where students’ needs, interests, and learning styles are prioritized. To better understand how students perceive a good teacher, this review comprehensively presents the perceptions of students at different educational levels on the traits of a good teacher. It discusses the nuances in these perceptions and whether they are justifiable. It reviewed more than 75 papers to achieve its aims. This review indicates that effective teachers possess characteristics like desirable personality, interpersonal skills, and instructional methods. It highlights the complex role teachers play in influencing students' academic and emotional growth. The shift from teaching skills in primary to relationship-oriented traits in secondary education shows that a student's developmental stage significantly affects their view of effective teaching. Secondary students often emphasize relational elements, such as appreciation and empathy, due to their need for autonomy and peer-like connections. University students value subject expertise, effective communication, and motivation. Like secondary students, they view traits like empathy, respect, and approachability as important.  The perceptions of a good teacher, particularly the ability to create a safe and supportive environment, relational skills, and competence in delivering content, are largely justifiable. However, the emphasis on rendering socio-emotional support and a student-consumer mentality in universities that prompts students’ needs to be prioritized could add to teachers’ already heavy workload and result in burnout. While serving as motivators, teachers themselves need motivation to perform their work more effectively.